Research progress on the mechanism of probiotics regulating cow milk allergy in early childhood and its application in hypoallergenic infant formula - Lin, Mao; Yanjun, Cong (Frontiers in Nutrition, 2024)
Some infants and young children suffer from cow's milk allergy (CMA), and have always mainly used hypoallergenic infant formula as a substitute for breast milk，but some of these formulas can still cause allergic reactions. In recent years, it has been found that probiotic nutritional interventions can regulate CMA in children. Scientific and reasonable application of probiotics to hypoallergenic infant formula is the key research direction in the future. This paper discusses the mechanism and clinical symptoms of CMA in children. This review critically examines the issue of how probiotics use intestinal flora as the main vector to combine with the immune system to exert physiological functions to intervene CMA in children, with a particular focus on four mechanisms: promoting the early establishment of intestinal microecological balance, regulating the body's immunity and alleviating allergic response, enhancing the intestinal mucosal barrier function, and destroying allergen epitopes. Additionally, it overviews the development process of hypoallergenic infant formula and the research progress of probiotics in hypoallergenic infant formula. The article also offers suggestions and outlines potential future research directions and ideas in this field.